Desenvolvimento de um sistema de controle de temperatura com pastilha Peltier para análise da eficiência de células fotovoltaicas - Veloso, Gabriel Nunhez (2024)
The sun is a vital source of energy for all living beings and is present in all parts of the world. Photovoltaic panels were created to transform the irradiation from the sun into a source of clean and renewable electrical energy. However, these panels still do not have high energy efficiency. The control of the incident temperature on a photovoltaic panel can result in an increase in its energy efficiency. In this work, temperature control over a photovoltaic cell is presented through a closed-loop control system based on cooling the cell with a Peltier module. To achieve this cooling with the objective of controlling the temperature on the photovoltaic cell, a code was developed in Arduino where it receives the temperature from the sensor, compensates for this temperature through a PID controller, and sends the result via a PWM signal to the IRF520 MOSFET module, which will control the voltage applied to the Peltier module and consequently the temperature it will reach. With the help of a measurement circuit consisting of an IRF540 MOSFET and a resistor, activated by the PWM circuit using the SG3524 IC, it was possible to obtain the current versus voltage graph of the photovoltaic cell for temperatures of 15, 25, 35, 45, and 55 ºC, thus proving that the maximum power occurred at the lowest temperature, as the cell's efficiency decreases with increasing temperature.